Optimalisasi Manajemen Kasus dengan Sistem Informasi Mahkamah di Pondok Pesantren Nurul Jadid - Nadiyah, Nadiyah; Hasanah, Uswatun; Ghufairoh, Siti (Universitas Nurul Jadid, 2024)
Managing violation and trial data at the Nurul Jadid Islamic Boarding School Court is still done manually, causing issues such as administrative delays, recording errors, and difficulty accessing data. This research aims to develop a web-based information system to enhance efficiency, accuracy, and ease of data management. Using the prototype development method, the process involved needs analysis, rapid design, prototype development, user evaluation, prototype refinement, and implementation. Results indicate that the system significantly improves the recording and reporting process, reduces errors, and ensures fast and accurate data access. Furthermore, the system enhances transparency and accountability in managing violation cases, positively impacting the Court's efficiency and effectiveness. This research provides a reference model for other educational institutions to develop similar systems to manage violation and trial data.